ESTIMASI PARAMETER PADA DISTRIBUSI EKSPONENSIAL - Renny Aulia; Noor Fajriah; Nur Salam (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2011)
Point estimation of a population parameter is a value obtained from relatedsample and used as an estimator of the parameter whose value is unknown. Pointestimator can be determined by using two methods: classical method (momentmethod and maximum likelihood) and Bayes method. The purpose of this researchis to determine the point estimation of an exponential distribution with oneparameter using Moment method, Maximum Likelihood method and Bayesmethod and determine the point estimation of an exponential distribution with twoparameters Moment method and Maximum Likelihood method.The method of this research is a literature study from various sources thatsupport and relevant to the topic.The result shows that the point estimation of Exponential distribution forone parameter by using Moment method and Maximum Likelihood Method isx , while the Bayes estimator of Exponential distribution for one parameter withprior konjugate Gamma distribution is   x  n pn pnii      11 and Chi Square is      2 21121kx nknnii. The point Estimation of exponential distribution for twoparameters by using the Moment method is 1 22ˆ Xnxnii  and1 22ˆ XnxXnii   , whereas by using the Maximum Likelihood method is nx xnin i  11:ˆand n x 1: ˆ  .